The summer of keeping secrets - Lynn, Jill (Love Inspired, 2024)
Recently widowed Marin Henderson considers time with her two adult children a gift. And she's intent on not prying into their lives while they're all together, cleaning out her late parents' Colorado home. But from the start, nothing goes as planned. Her free-spirited daughter, Slade, and her strait-laced son, Reed, both arrive ahead of schedule, and no one is explaining why. Marin knows they're hiding issues in their personal lives. But she can only push so far because she, too, is keeping secrets. Setting aside family tensions, the three of them get to work purging the house. But when Slade discovers a decades-old newspaper clipping about a body found on the rocks below the house, questions arise. Marin insists the death was ruled an accident, but Slade's curiosity is piqued. And when a roof leak compels Marin to call on an old friend and flame for help, it's the catalyst for a wave of revelations. Between a daughter bent on distracting herself from her own career turmoil, a son desperate to hold on to his marriage and a mother forced to confront her choices from that long-ago summer, pieces of the past and present begin to unravel. And before the summer is over, they each must decide what to hold on to and what to let go.